2002
DOI: 10.1179/016164102101199675
|View full text |Cite
|
Sign up to set email alerts
|

Limbus lumbar and sacral vertebral fractures

Abstract: We evaluated the fractures of the lumbar and sacral vertebral limbus by disc impingement at the peripheral ring apophysis in 23 adults associated with trauma in 16 of them. Lumbalgia, radicular pain and narrow canal symptoms are the presenting forms of this underdiagnosed pathology. CT is the best method of examination, while plain roentgenograms and MR are usually negative. Accurate diagnosis and surgical technique with larger exposure are needed to resect the fractured fragments and protruded disc material f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…Epstein et al [4] showed that trauma played a significant etiologic role in up to onehalf of the patients in their study. Mendez et al [20] found 60 % of traumatic antecedents ranging from simple falls to strenuous activities. However, many patients had not recalled a history of recent trauma episode or just complained of the symptoms many years previously.…”
Section: Pathogenesismentioning
confidence: 99%
See 4 more Smart Citations
“…Epstein et al [4] showed that trauma played a significant etiologic role in up to onehalf of the patients in their study. Mendez et al [20] found 60 % of traumatic antecedents ranging from simple falls to strenuous activities. However, many patients had not recalled a history of recent trauma episode or just complained of the symptoms many years previously.…”
Section: Pathogenesismentioning
confidence: 99%
“…Diagnostic accuracy rate may be affected by the age of the patient, the affected level, the size and shape of the fragment. Computed tomography (CT) scan has the best performance for the demonstration of the size, shape and location of fracture [1,20,35] (Fig. 2).…”
Section: Radiological Diagnosismentioning
confidence: 99%
See 3 more Smart Citations